Inequalities in measles immunization coverage among two-year-olds in Sierra Leone, 2008–2019 - Augustus Osborne; Alpha Umaru Bai-Sesay; Umaru Sesay; Alieu Tommy; Camilla Bangura; Bright Opoku Ahinkorah (BMC Infectious Diseases)
Abstract Background Measles, a highly contagious and potentially fatal disease, remains a significant public health concern, particularly in low- and middle-income countries. Vaccination is the most effective way to prevent measles and achieving high immunization coverage is crucial for protecting children and communities. This study investigated the trends and inequalities in measles immunization coverage among two-year-olds in Sierra Leone between 2008 and 2019. Methods The study utilized data from the Sierra Leone Demographic Health Surveys conducted in 2008, 2013, and 2019. The World Health Organisation Health Equity Assessment Toolkit was used to calculate various inequality measures, including Difference (D), Ratio (R), Population Attributable Risk (PAR), and Population Attributable Fraction (PAF). An inequality assessment was conducted for six stratifiers: age, economic status, level of education, place of residence, sex of the child, and sub-national province. Results In Sierra Leone, measles immunization coverage increased between 2008 and 2013 and decreased slightly in 2019. In 2008, 66.2% of two-year-olds were immunized, which increased to 86.2% in 2013 and then fell slightly to 82.2% in 2019. There was a decrease in inequality for age from 4.2 percentage points in 2008 to 3.0 percentage points in 2019 (D = 4.2 in 2008 and 3.0 in 2019). Economic-related inequality decreased from 8.1 percentage points in 2008 to 7.5 percentage points in 2019 (D = 8.1 in 2008 and 7.5 in 2019). Inequality in education decreased from 10.3 percentage points in 2008 to 7.4 percentage points in 2019 based on results from the inequality measure D. For place of residence, inequality decreased from 6.0 percentage points in 2008 to 4.0 percentage points in 2019. For the child’s sex, the inequality increased from 1.9 percentage points in 2008 to 4.5 percentage points in 2019. The PAF revealed that the setting average could have been 1.4% higher in 2008 and 2.7% higher in 2019 without the child’s sex inequality. Provincial inequality decreased from 19.4 percentage points in 2008 to 16.9 percentage points in 2019 (D = 19.4 in 2008 and 16.9 in 2019). Conclusion The observed fluctuations in national measles immunization coverage for children under two underscore the need for sustained efforts in vaccination programs. While improvements in access based on age, socioeconomic status, education level, and place of residence suggest progress in reducing inequalities, the persistent provincial disparities, with a significant gap in 2019, highlight ongoing challenges that must be addressed to ensure equitable health outcomes. Additionally, the increase in inequalities based on the child’s sex during the study period raises concerns about targeted interventions that may inadvertently neglect specific groups. These findings imply that policymakers must prioritize strategies that maintain high vaccination rates and focus on closing the geographical and sex-based gaps, particularly in underserved provinces and among vulnerable populations.